Mathematics Teacher Performance Based on the Perceptions and Competence of Junior High School Students in Labuhanbatu District - Nur Indah Puspita Sari; Sakinah Ubudiyah Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to see the strengths and weaknesses of the teacher in the teaching process based on the competence aspects of the mathematics teacher and to describe the situation and state of the teacher's competence when in the learning process in the classroom based on student perceptions associated with the competence of the students themselves. Data processing techniques using data analysis Structural Equation Modeling (SEM). The population of this study were junior high school students in Labuhanbatu. The sampling technique used was proportional random sampling leading to simple random sampling, the number of samples obtained was 219 students. Techniques in the data collection process were carried out by distributing a questionnaire on students' perceptions of the mathematics teacher's performance consisting of 48 questions in the form of a Likert scale.